A small child’s upbringing in the first decade of the interwar period in Poland in some of the pedagogical periodicals – continuations and changes - Kozłowska, Małgorzata (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2015)
The main aim of this article was comparing some aspects of the upbringing of pre-school children, which were described in Warsaw periodicals (like: „Bluszcz”,„Opieka nad Dzieckiem” and „Dziecko i Matka”) in the interwar period with the relevant areas after the war described in magazines like: „Bluszcz”, „Wychowanie w Domu i Szkole” and „Dziecko. Czasopismo poświęcone wychowaniu domowemu i społecznemu”. There were three fields of analysis: childcare and healthcare, moral upbringing and pedagogical methods. The main differences were found in the sphere of healthcare, children’s obedience and their self-development. The changes were connected with the decreased number of children in Poland after the First World War and the new family model spreading in Western Europe.
Keywords: interwar period; childcare; healthcare of children; interwar periodicals